(untitled) (University of Khartoum Engineering Journal, 2022)
This paper presents a neuro-fuzzy controller design for speed control of DC motor. The most commonly used controller for the speed control of dc motor is the conventional Proportional-Integral-Derivative (PID) controller. The PID controller has some disadvantages like: high overshoot, sensitivity to controller gains and slow response. Fuzzy control and neuro-fuzzy control are proposed in this study. The performances of the two controllers are compared with PID controller performance. In this paper, neural networks are used in a novel way to solve the problem of tuning a fuzzy logic controller. The neuro fuzzy controller uses neural network learning techniques to tune membership functions. For the speed control of dc motor drives, it is observed that neuro-fuzzy controller gives a better response compared to other controllers.